Paederoside, an active metabolite of Paederia scandens, alleviates osteoporosis by modulating Wnt/β-catenin signaling - Liu, Zhize; He, Weitao; Zhang, Jingwei; Su, Bo; Mu, Jiang; Wang, Xintao (Frontiers in Pharmacology, 2025)
IntroductionPaederia scandens (Lour.) Merr. (P. scandens), a widely consumed edible wild botanical drug in East Asia, has traditionally been used in folk medicine for its purported health-promoting effects, including the relief of fractures, rheumatoid arthritis, and pain. Despite its common use, the bioactive metabolites and underlying mechanisms of action remain insufficiently understood. This study investigates the pharmacological effects and molecular mechanisms of P. scandens in the context of osteoporosis.MethodsAn ovariectomized (OVX) rat model of osteoporosis was used to evaluate the effects of P. scandens extract on bone health. Network pharmacology analysis identified candidate metabolites related to osteoblast differentiation. Paederoside, the primary plasma-absorbed metabolite, was validated in OVX rats via HPLC-Q-TOF-MS. In vitro experiments assessed osteogenesis and osteoclast activity using an osteoblast-osteoclast co-culture system, while in vivo studies evaluated serum calcium and phosphorus levels, bone morphology, and bone mass.ResultsP. scandens extract significantly improved bone mass, bone mineral density (BMD), and the trabecular bone microstructure in the OVX rat model. Paederoside promoted osteogenesis and suppressed osteoclast activity in vitro. In vivo, paederoside demonstrated pronounced anti-osteoporotic effects, as evidenced by elevated serum calcium and phosphorus levels, improved bone morphology, and increased bone mass. Paederoside upregulated osteogenesis-related markers (BMP2, Smad1, Col1a1, Bglap, Osterix, and Runx2) and downregulated osteoclastogenesis-related markers (RANKL, NFATc1, Acp5, Ctsk, and Mmp9). Transcriptomic analysis revealed that paederoside modulated the Wnt/β-catenin signaling pathway, inducing Wnt3a expression, inhibiting GSK-3β and β-catenin phosphorylation, and upregulating downstream targets such as Cyclin D1 and c-Myc.DiscussionIn conclusion, P. scandens exerts protective effects against osteoporosis, and paederoside, identified as a primary plasma-absorbed metabolite, enhances osteoblastogenesis and suppresses osteoclastogenesis, likely through the upregulation of the Wnt/β-catenin signaling pathway. This study elucidates the health benefits of P. scandens and paederoside in the prevention and treatment of osteoporosis.